Perancangan UI/UX Aplikasi Kasir Inklusif untuk Penyandang Disabilitas di Coffee Shop - Aldian Umbu Tamu Ama; Ricky Arnold Nggili; Deva Nita Mulya; Yashinta Putri Dwi Astuti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Kopi Hening is a coffee business in Salatiga City managed by individuals who are deaf or hard of hearing. Facing challenges in customer communication and manual bookkeeping processes, this study aims to design a prototype UI/UX for an inclusive cashier application to enhance operational efficiency and bookkeeping accuracy. Using the Design Science Research Methodology (DSRM) approach, the study involved direct observation of cashier activities, interviews with supervisors, and design evaluation through simulations using the Cognitive Walkthrough method. The Cognitive Walkthrough evaluation, which measured user success rates in completing specific tasks, showed good performance with transaction scenarios achieving 83-86% success rates (cash payment 83%, transfer 83%, QRIS 86%) and financial bookkeeping scenarios reaching 73%. Expert evaluations confirmed that the design adheres to inclusive UI/UX principles, though further adjustments, such as optimizing text size and element spacing, are recommended for better accessibility. This study serves as an initial step toward supporting digital inclusion and provides a foundation for the future development of inclusive cashier applications.